Flow (LEARNing Landscapes, 2007)
What is student engagement? How do teachers engage their students? As a way to address these questions, I used collage as an arts-informed method for exploring the subject of student engagement.The collages are displayed and I describe the process of producing this work.
Keywords: student engagement; collage; arts-informed